Supercritical CO2 Extraction from Bacupari (Garcinia brasiliensis) and Leiteira (Tabernaemontana catharinensis) Seeds - Lopes, Guilherme de Souza [UNESP]; Conceição, Matheus Almeida [UNESP]; Hiranobe, Carlos Toshiyuki [UNESP]; da Silva, Camila; da Silva, Erivaldo Antônio [UNESP]; dos Santos, Renivaldo José [UNESP]; Ferreira-Pinto, Leandro [UNESP] (MDPI, 2025)
This study evaluated the extraction of oils from the seeds of bacupari (Garcinia brasiliensis Mart.) and leiteira (Tabernaemontana catharinensis), using carbon dioxide (CO2) in the supercritical state. The effects of temperature (40, 50, and 60 °C) and pressure (20, 24, and 28 MPa) on the yield and extraction kinetics were investigated. The results indicated that, within the studied limits, temperature had a negligible influence on the process, while pressure had a greater impact on the yields owing to its effect on the density of supercritical CO2 and the solubility of the extracted compounds. The maximum yields obtained were 14.8% for bacupari and 15.2% for leiteira, with most of the oil extracted within the first 30 min, indicating initial rapid extraction. Chemical composition analysis revealed relevant bioactive compounds in bacupari, including oleic acid (35%) and delta-tocopherol (19.6%). In leiteira, the main compounds identified were hexanedioic acid (29.2%) and stigmast-5-ene (7.95%). These results suggest the potential application of these oils in the pharmaceutical, cosmetic, and food sectors, while also highlighting the feasibility of using supercritical CO2 as an extraction method for these plant matrices.